Development of a case method learning model to hone students' translation competence in language teaching courses - Siregar, Masitowarni; Husein, Rahmad; Putra, Surya Kelana (UNIB Press, 2024)
In 2020-2024, the Ministry of Education and Culture launched one of the main objectives of developing a strategic plan, namely optimizing the quality of learning in innovative forms in order to realize student success in achieving maximum learning outcomes that include attitudes, knowledge and skills. Hodijah, S & et al (2022) argue regarding the development goals of the Ministry of Education and Culture that the expected innovative learning can be implemented from learning created in the form of collaborative and participatory classes. Furthermore, according to the 2022 edition of EF English First Proficiency, Indonesia is in 81st place out of 111 countries with a score of 469 which falls into the Low Proficiency category in every aspect of the English language, one of which is Translation. Based on these things, to overcome the low level of students' English proficiency, especially in terms of Translation and to answer the demands of the Ministry of Education and Culture for Higher Education in creating innovative classes . It is recommended for lecturers to use the Case Study learning model because it has been proven to be effective in improving translation skills in various previous studies. Based on these things, this research aims to developCase Study Learning to Improve Students' Translation Ability in the Translation in English Language Teaching (ELT) Course, Department of English Language and Literature, Medan State University The development of the Case Study Learning Model was carried out using the ADDIE Development model which consists of 5 stages, namely; (1) Needs analysis, (2) Design of the Case learning model 3) Development of the Case Study Learning Model in Translation in ELT Learning (4) Implementation, namely trial of the Case Study learning model in the Translation in ELT course (5) Evaluation of Case Study model-based learning . This research uses a qualitative and quantitative descriptive approach in analyzing data. Validity tests, Practicality Tests and Effectiveness Tests was carried out on the development product to ensure that the Case Study Learning Model developed valid, practical and effective in improving students' translation skills in the Translation in ELT course. The results of the research show that the model developed is valid, practical and effective.